2015
DOI: 10.1007/978-94-017-9849-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Use of Calibrated ITRAX XRF Data in Determining Turbidite Geochemistry and Provenance in Agadir Basin, Northwest African Passive Margin

Abstract: The Agadir Basin is a mixed siliciclastic-volcaniclastic deepwater turbidite system derived from several sedimentary sources. Estimating the influence of these sources requires detailed geochemical profiles of sediment cores. This is achieved using an ITRAX µXRF core scanner that normally produces elemental profiles in units of counts or count rate. Improved insights are achieved if the ITRAX data are calibrated to produce concentration data. Turbidite geochemistry can then be used to more reliably infer the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
1
21
1
Order By: Relevance
“…both observed minor increases in Pearson's R value between XRF-CS and ED-XRF of Ca, whereas inMaclachlan et al (2015) and this study, Ca correlation coefficients decreased slightly after water content correction. Carbonate content in cores examined byTjalingii et al (2007) was high at 30-65 wt %, whereas cores examined by andMaclachlan et al (2015) generally ranged from about 5-15 wt % and carbonate content in Harvey Lake was < 1 wt %. Standards analyzed by Bureau Veritas showed that ICP-MS-measured Ca concentrations are accurate to actual concentrations within the 90% confidence interval, indicating ICP-MS accurately reproduced Ca trends in sediment.…”
contrasting
confidence: 56%
See 4 more Smart Citations
“…both observed minor increases in Pearson's R value between XRF-CS and ED-XRF of Ca, whereas inMaclachlan et al (2015) and this study, Ca correlation coefficients decreased slightly after water content correction. Carbonate content in cores examined byTjalingii et al (2007) was high at 30-65 wt %, whereas cores examined by andMaclachlan et al (2015) generally ranged from about 5-15 wt % and carbonate content in Harvey Lake was < 1 wt %. Standards analyzed by Bureau Veritas showed that ICP-MS-measured Ca concentrations are accurate to actual concentrations within the 90% confidence interval, indicating ICP-MS accurately reproduced Ca trends in sediment.…”
contrasting
confidence: 56%
“…Comparison of wt % organic matter to Coh/Inc scatter from the Harvey Lake samples did not show a strong correlation (τ = -0.43, n = 61; Figure 3.3). Other researchers have shown that there is negligible impact on the XRF-CS signal if water content or large sediment grains constitute < 25 wt % of a sample (Maclachlan et al 2015). It is possible that a similar relationship is true for organic content, although this was not quantified by Maclachlan et al (2015).…”
Section: Elementmentioning
confidence: 94%
See 3 more Smart Citations